2016
DOI: 10.1039/c5ob02469b
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed tandem Ullmann type C–N coupling and dehydrative cyclization: synthesis of imidazo[1,2-c]quinazolines

Abstract: A simple and efficient one-pot protocol has been demonstrated for the synthesis of imidazo[1,2-c]quinazoline derivatives through a copper catalyzed tandem reaction between substituted 2-(2-bromophenyl)-1H-imidazoles and formamide. The synthetic protocol involves initial Ullmann-type C-N coupling followed by intramolecular dehydrative cyclization. The method uses readily available 2-(2-bromophenyl)-1H-imidazoles as the starting materials to afford imidazo[1,2-c]quinazolines in moderate to good yields and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 40 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…The present reaction seems to proceed via an initial formation of CN coupled intermediate 4 by copper‐catalyzed Ullmann‐type coupling between 1a and 2 , which triggers cyclization and dehydration to give 2‐(2‐bromophenyl)‐1 H ‐indole 3 (Scheme ) . It is reported that N‐substituted o ‐bromobenzamides and 2‐(2‐bromoaryl)‐1 H ‐imidazoles are found to be coupled and cyclized with primary amides in the presence of CuI to give quinazolinones and imidazo[1,2‐ c ]quinazolines . We confirmed in a separate experiment that CN coupled intermediate 6 is formed in 56% yield from 2‐(2‐bromophenyl)‐1‐methyl‐1 H ‐indole ( 5 ) and 2d under the employed conditions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…The present reaction seems to proceed via an initial formation of CN coupled intermediate 4 by copper‐catalyzed Ullmann‐type coupling between 1a and 2 , which triggers cyclization and dehydration to give 2‐(2‐bromophenyl)‐1 H ‐indole 3 (Scheme ) . It is reported that N‐substituted o ‐bromobenzamides and 2‐(2‐bromoaryl)‐1 H ‐imidazoles are found to be coupled and cyclized with primary amides in the presence of CuI to give quinazolinones and imidazo[1,2‐ c ]quinazolines . We confirmed in a separate experiment that CN coupled intermediate 6 is formed in 56% yield from 2‐(2‐bromophenyl)‐1‐methyl‐1 H ‐indole ( 5 ) and 2d under the employed conditions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…In continuation of our interest in developing methodologies for the synthesis of N ‐heterocycles, we previously reported the synthesis of azole‐fused imidazo[1,2‐ a ]pyridines (Scheme e) and naphtho‐fused imidazo[1,2‐ a ]pyridines via copper and palladium‐catalysed one‐pot tandem reactions. Herein, we report an alternative and more versatile protocol for the synthesis of highly functionalized azole‐fused imidazo[1,2‐ a ]pyridines through a sequential three‐component imidazole/benzimidazole formation followed by a copper‐catalyzed intramolecular Ullmann type C–N coupling and their photophysical properties (Scheme f).…”
Section: Introductionmentioning
confidence: 99%
“…7 While the present work was being performed, such a similar coupling and cyclization reaction leading to imidazo[1,2- c ]quinazolines was also exemplified by the reaction of 2-(2-bromoaryl)-1 H -imidazoles and formamide under CuI catalysis. 8 As part of our continuing studies directed toward transition-metal-catalyzed synthesis of N-fused hybrid scaffolds, 4,9 we provide here a new synthetic method for benzo[4,5]imidazo[1,2- c ]-pyrimidines and -quinazolines by copper-catalyzed coupling and cyclization of 2-(2-bromovinyl)- and 2-(2-bromoaryl)-benzimidazoles with primary amides as building blocks. In addition, this report also shows the synthesis of unprecedented N-fused hybrid scaffolds, benzo[4,5]imidazo[1,2- c ]pyrimidin-6,9-diones (Scheme 1, C ) and benzo[4,5]imidazo[1,2- c ]quinazoline-8,11-diones (Scheme 1, D ), from methoxy-substituted A and B derivatives on benzimidzole moiety.…”
Section: Introductionmentioning
confidence: 99%